Distribusi Pola Luka Korban Meninggal Pada Kasus Kecelakaan Lalu Lintas Di RSU Kabupaten Tangerang Tahun 2023 - Engkolan, Cherine Zefanya; Liauw, Djai Yen; Hon, Handy Winata (Jurnal MedScientiae, 2025)
A traffic accident is an event that occurs on a highway where a motor vehicle, rider pedestrian, or other user is involved in an impact or collision that causes physical damage, injury, and or death. Based on the Central Bureau of Statistics, traffic accidents that occurred in Indonesia in 2021 were 103,645 cases. The purpose of this study is to analyze the distribution of injury patterns experienced by traffic accident victims in Tangerang during the period of 2023. This study used descriptive retrospective method to identify the types of injury. The results showed that head injury (36,5%) was the most common type of injury, followed by upper extremity (25,7%). In addition, it was found that males were more frequently victimized than females, and the age group of 15-39 years had the highest prevalence of traffic accidents. This study provides important insights for authorities in designing traffic safety policies and improving emergency medical services.